2010
DOI: 10.1097/hjh.0b013e328334b39e
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension in rural China: results from Shandong Province

Abstract: In the study population, the prevalence of hypertension is high, but levels of awareness, treatment and control are unacceptably low. There is an urgent need for comprehensive integrated strategies to improve prevention, detection and treatment of hypertension in rural areas in Shandong Province, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 12 publications
4
52
2
Order By: Relevance
“…The prevalence were 46.6% in Beijing population aged 45 years or above, 37.8% in Liaoning population aged 35 years or above, 43.8% in rural Shandong population aged 25 years or above and 42.0% in inner Mongolian aged 35 years above (references). [5][6][7][8] The prevalence in our population was similar to that in a rural Central Indian population of ages 30+ years in India, which is also a large developing country (reference). 23 Compared to the prevalence of hypertension (around 30%) in adults aged 18 years or above in the United States, 24 our adult population aged 20 years old or above had a relatively lower prevalence (20.5%).…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence were 46.6% in Beijing population aged 45 years or above, 37.8% in Liaoning population aged 35 years or above, 43.8% in rural Shandong population aged 25 years or above and 42.0% in inner Mongolian aged 35 years above (references). [5][6][7][8] The prevalence in our population was similar to that in a rural Central Indian population of ages 30+ years in India, which is also a large developing country (reference). 23 Compared to the prevalence of hypertension (around 30%) in adults aged 18 years or above in the United States, 24 our adult population aged 20 years old or above had a relatively lower prevalence (20.5%).…”
Section: Discussionsupporting
confidence: 79%
“…5,6 The InterASIA Collaborative Group reported that 27.2% of the Chinese adult population aged 35 to 74 years had hypertension in 2000 to 2001. Results from a cross-sectional study conducted in 2007 by Li and colleagues 14 revealed that the prevalence of hypertension was 43.8% in rural residents 25 years and older. A similar trend was also found in India.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference associated with age group or gender. These rates are between 15.2 and 47.7% in Europe, [20][21][22][23] 19.6% in Brazil, 24 3.9 and 30.6% in China [25][26][27] and 50.1% in the United States, as determined by the National Health and Nutrition Examination Survey 2007-2008. 28 The signs and symptoms presented on admission to the hospital vary according to the clinical presentation of HC, depending on which target organs are affected most severely.…”
Section: Discussionmentioning
confidence: 99%